The prevalence of JAK2, CALR, and MPL mutations in BCR-ABL1 rearrangement negative Iraqi patients - Aseel M. Al Dayyeni; Bassam T. Al-Gailani; Mohammed Ghanim Mahdi; Mushtaq M. Khazeem (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Purpose: To date, there is no enough data about the prevalence of JAK2, CALR, and MPL mutations in BCR-ABL1 rearrangement negative myeloproliferative neoplasms (MPN) patients in Iraq. This study was conducted to determine the prevalence of these mutations and to evaluate the clinical features of polycythemia vera (PV) and essential thrombocythemia (ET) patients in Iraq. Methods: we evaluated the presence of JAK2, CALR, and MPL mutations in 158 patients. JAK2V617F mutation was assessed using either Allele specific PCR or quantitative PCR. JAK2 negative MPN patients were further assessed for the existence of CALR, MPL, or JAK2 exon 12 mutations by quantitative PCR. Results: JAK2V617F mutation was detected in 97.9% and 61.7% of PV and ET patients respectively, while JAK2 exon 12 was found in 2.1% of PV patients. CALR mutation was identified in 38.3% of ET patients. PV patients had higher level of hemoglobin, hematocrit, WBC, and neutrophil counts, and had lower levels of platelet count when compared to ET. CALR mutation was more prevalent in younger age groups, while JAK2V617F mutation predominantly found in older age groups. Greater number of PV patients (34.7%) developed splenomegaly at diagnosis than ET (12.7%). More thrombotic events were observed in PV than ET patients, but the result did not reach statistical significance. Conclusion: The incidence of JAK2V617F, JAK2 exon 12, and CALR mutations in Iraqi MPN patients was similar to the previously published literature. In addition, we reconfirmed some clinical features of PV and ET patients described in literature.